2002
DOI: 10.1115/1.1455030
|View full text |Cite
|
Sign up to set email alerts
|

Stability Prediction for Low Radial Immersion Milling

Abstract: Traditional regenerative stability theory predicts a set of optimally stable spindle speeds at integer fractions of the natural frequency of the most flexible mode of the system. The assumptions of this theory become invalid for highly interrupted machining, where the ratio of time spent cutting to not cutting (denoted ρ) is small. This paper proposes a new stability theory for interrupted machining that predicts a doubling in the number of optimally stable speeds as the value of ρ becomes small. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(92 citation statements)
references
References 10 publications
1
90
0
1
Order By: Relevance
“…In addition to Hopf bifurcations, period doubling bifurcations are also a typical form of instability, as it was shown analytically by Insperger and Sté-pán [21], Corpus and Endres [29], Bayly et al [22], Davies et al [20], via numerical simulation by Zhao and Balachandran [26], and confirmed experimentally by Bayly et al [22] and Davies et al [20]. The nonlinear analysis of Stépán and Szalai [30] showed that this period doubling bifurcation is also subcritical.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to Hopf bifurcations, period doubling bifurcations are also a typical form of instability, as it was shown analytically by Insperger and Sté-pán [21], Corpus and Endres [29], Bayly et al [22], Davies et al [20], via numerical simulation by Zhao and Balachandran [26], and confirmed experimentally by Bayly et al [22] and Davies et al [20]. The nonlinear analysis of Stépán and Szalai [30] showed that this period doubling bifurcation is also subcritical.…”
Section: Introductionmentioning
confidence: 97%
“…Usually, a finite dimensional approximate transition matrix is used to predict stability properties. Several analytical methods have been developed to determine the stability boundaries for milling [11,[17][18][19][20][21][22][23]. Numerical simulation can also be used to capture the interrupted nature of the milling process [24][25][26][27][28], but the exploration of parameter space via time domain simulation is inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The contact time ρτ is considered to be so short that the position of the tool, and also the chip thickness, do not change during this time. Davies et al [2000Davies et al [ , 2002, and Bayly et al [2001] analyzed this approximation theoretically and experimentally, too. The equations of motion can be constructed for the two parts of the tool motion in the following way.…”
Section: Nonlinear Modeling Of Millingmentioning
confidence: 99%
“…Merdol and Altintas [2] put forward the multifrequency solution for low radial immersion milling. Davies et al [3] utilized the time-domain solution technique for predicting the stability of highly interrupted machining. Mann et al [4] took advantage of the temporal finite element analysis (TFEA) method in order to approximate the milling process more accurately, which made it possible for obtaining the surface location error and stability simultaneously.…”
Section: Introductionmentioning
confidence: 99%